16 Dr. (12th November 2018) - Kelendar, Hisham; Mohammed, Mohammed
Abstract : Medical practices tend to develop and grow. Today, healthcare is 'characterized by more to know, more to do, more to manage, more to watch, and more people involved than ever before'. The aging population, chronic diseases, increase demand, new technology and expensive services made different organizations under pressure. In this era, providing health services in high quality and achieving patient expectation with minimum resources considers as a challenge. Therefore, a new way of providing the healthcare services must be adopted. In the literature, many managerial initiatives adopted in healthcare system (HCS) such as Total Quality Management, Balanced Scorecard and Six Sigma. Lean is one of those main influential management approaches recently adopted in HCS. Lean (porn in the industrial sector) promises to provide more with less. Four common themes identified from lean philosophy: process-based view, focus on value, eliminating waste and employee-driven change. The healthcare setting, where it allows the authorisation of a decentralised management style is directly associated with successful lean implementation. The literaturehighlighted on how the leadership is critical for lean work to be successful. This could explain why adopting lean superficially without the leadership support and commitment, the gain will be temporary. Practical action from the senior leaders is by being actively involved in the lean events, expressing their attention for the worker's ideas and views, being a facilitator for eliminating the barriers, facilitate the corrective actions implementation, shows empathy and appreciation of the worker's efforts for improving the organisation and so on. Therefore, it is vital to have an effective lean leadership to ensure a successful lean transformation over the long-term. The researcher aims to explore the case of lean in Kuwait HCS by applying lean to diabetic patient's flow in Primary Healthcare Centres considering the leadership.